2009
DOI: 10.2166/wh.2009.060
|View full text |Cite
|
Sign up to set email alerts
|

Too much or too little? A review of the conundrum of selenium

Abstract: Chemical elements such as selenium, fluoride, iron, calcium and magnesium are essential to the human being, although some are toxic when absorbed in high doses. In this paper, the risks associated with insufficient and excessive intake of selenium in the diet are reviewed, focusing on drinking water. Two different approaches are used to derive recommended nutrient intakes (RNI) for adequate nutritional status and guideline values to prevent excessive exposure. The former is based on the daily intake which meet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 65 publications
1
19
0
1
Order By: Relevance
“…While the primary emphasis of selenium research has been on evaluating the potential benefits of its antioxidant and anticancer effects, 5-9 recent findings from observational studies and randomized clinical trials have suggested an association between moderate to high selenium exposure and adverse cardiometabolic effects, at least in populations with adequate selenium intake such as the US. [86][87] Therefore, the apparently puzzling evidence [88][89] on the full range of effects, either beneficial or detrimental, of selenium exposure on chronic disease endpoints might be explained by the variability of selenium status and selenium dietary intakes across different countries and population subgroups. In this view, the association between selenium and cardio-metabolic outcomes is likely to be U-shaped with potential harm occurring at selenium levels both below and above the physiological range for optimal activity of selenoproteins.…”
Section: Perspectivesmentioning
confidence: 99%
“…While the primary emphasis of selenium research has been on evaluating the potential benefits of its antioxidant and anticancer effects, 5-9 recent findings from observational studies and randomized clinical trials have suggested an association between moderate to high selenium exposure and adverse cardiometabolic effects, at least in populations with adequate selenium intake such as the US. [86][87] Therefore, the apparently puzzling evidence [88][89] on the full range of effects, either beneficial or detrimental, of selenium exposure on chronic disease endpoints might be explained by the variability of selenium status and selenium dietary intakes across different countries and population subgroups. In this view, the association between selenium and cardio-metabolic outcomes is likely to be U-shaped with potential harm occurring at selenium levels both below and above the physiological range for optimal activity of selenoproteins.…”
Section: Perspectivesmentioning
confidence: 99%
“…Selenium (Se) is an essential element for human and animal health, but excess consumption may also be toxic, and the concentration range from trace element requirement to lethality is narrow (Ohlendorf et al, 1986;Läuchli, 1993;Spallholz, 1994;Arteel and Sies, 2001;El-Bayoumy, 2001;Tapiero et al, 2003;Schomburg et al, 2004;Gore et al, 2010;Fairweather-Tait et al, 2011). In animals, trace amounts of Se are required to form selenoenzymes, including a number of thioredoxin reductases and glutathione peroxidases.…”
mentioning
confidence: 99%
“…Chemical elements such as selenium, fluoride, iron, calcium and magnesium are essential to human beings even though some are toxic when absorbed in high doses (Gore et al 2010). Among them, Se has various beneficial effects such as antioxidant, antitumor, antiulcer, and anti-inflammatory effects (Rayman 2000;Duntas 2009;Bhattacharya et al 2011;Kim et al 2011).…”
Section: Discussionmentioning
confidence: 99%